Academic performance and its associated factors among khat-chewer and non-khat chewer high school students in Ethiopia, 2023 - Tesfa, Tilahun; Mossie, Tilahun Belete; Tadesse, Meseret; Guracho, Yonas Deressa; Munie, Birhanu Mengist (Frontiers in Psychiatry, 2025)
BackgroundAcademic performance measures student achievement and is assessed using school exams and ongoing evaluations. Regular khat consumption can negatively affect neurocognitive function, decision-making, and problem-solving abilities, leading to decreased academic achievement, especially in Ethiopia. This study aimed to assess academic performance and associated factors among khat chewer and non-khat chewer high school students in Motta in northwestern Ethiopia in 2023.MethodsA comparative cross-sectional study was conducted between April 26, and June 10, 2023, among 663 high school students, of whom 221 were khat chewers and 442 were non-chewers. A multistage sampling method was used to select participants. A structured, self-administered questionnaire was used to assess students’ academic performance. Data were analyzed using IBM SPSS version 25. Ordinal logistic regression analysis was performed at P < 0.05 with a 95% confidence interval to identify statistically significant variables.ResultsThe study participants, 45 (20.7%) Khat chewers and 41 (9.4%) non-chewers, had failed/poor academic performance. Of the students who scored less than 50% on one subject, 83 were (38.2%) khat chewers and 107 (24.6%) were non-chewers. The mean of academic performance was 59.82 and 66.45 for khat chewers and non-chewers, respectively. The findings showed that the chance of having an excellent academic performance was 35% lower for female students [AOR=0.65:95%CI: -0.819–0.055] and 45% lower for those unsatisfied with their school environment [AOR: 0.55, 95% CI: -1.014–0.173]. The chance of having an excellent academic performance was 6.43 times higher for those whose fathers had an educational grade of 7–12 [AOR: 6.43, 95%CI: 1.098–2.624] and 6.59 times higher for those with fathers who had a diploma [AOR: 6.59, 95% CI: 1.026–2.745], 8.01 times higher for those with a family income of 2001–5000ETB [AOR=8.01:95% CI: 1.479–2.683], 2.07 times higher for those with no alcohol use disorder [AOR: 2.07, 95% CI: 1.21–2.93], and 6.84 times higher for those with no depressive disorders [AOR: 6.84, 95% CI: 1.056–2.791].ConclusionsAcademic performance was lower among khat chewers than among non-khat chewers, and was affected by factors such as family income, father’s educational status, classroom environment, depression, anxiety, and alcohol use disorder. Enhancing school-community relations and increasing awareness can enhance academic performance.